Measuring impacts of “rat-running” driver behaviour in urban environment using GPS-based traffic data - Macedo, Eloísa (2020)
On specific congested sites of cities, drivers, attempting to minimize their own travel time, use secondary roads instead of the main roads. This rat-running behaviour may affect network performance, but little research has been conducted in this topic. The present study explores rat-running network impacts and suggests evaluation of network performance in a global perspective with respect to travel time, pollutant and noise emissions, and also road safety. For this purpose, vehicle dynamics data need to be collected, which is relatively easy to obtain through GPS-based traffic data. A case study involving a secondary residential road with intersections, high slope and narrow sections was selected for testing the proposed approach. Different scenarios of mitigating measures that could be implemented within the study area to reduce the number of rat-running drivers (rat-runners) are explored using the traffic simulation modelling software VISSIM. Results show implementing a single network intervention/redesign measure at local level may minimize externalities, but may not be sufficient. This study will allow traffic planners and designers to rethink certain measures to reduce the number of rat-runners moving through specific areas.